2020
DOI: 10.1177/1077559520910806
|View full text |Cite
|
Sign up to set email alerts
|

Child Maltreatment Investigations in Canada: Main and Moderating Effects of Primary Caregiver Cognitive Impairment

Abstract: Children of parents with cognitive impairment are overrepresented in the child protection system (CPS). The aim of this study was to examine the relationship between primary caregiver cognitive impairment (CCI) and CPS investigation outcomes using the Canadian Incidence Study of Reported Child Abuse and Neglect (CIS-2008). The CIS-2008 includes process and outcomes data on a national sample of CPS investigations involving a total of 15,980 children under the age of 16 years. This secondary data analysis found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 33 publications
2
29
0
Order By: Relevance
“…Longer term outcomes, including service referrals, are not known. Notably, cases featuring parents with CI are more likely to be kept open for ongoing child welfare services (McConnell et al, 2020), due perhaps to perceived complexity. It is possible that, after an extended period of assessment, additional referrals would be made in these cases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Longer term outcomes, including service referrals, are not known. Notably, cases featuring parents with CI are more likely to be kept open for ongoing child welfare services (McConnell et al, 2020), due perhaps to perceived complexity. It is possible that, after an extended period of assessment, additional referrals would be made in these cases.…”
Section: Discussionmentioning
confidence: 99%
“…Despite research showing that, with appropriate supports, most parents with CI can provide a level of care acceptable by community standards, high rates of child removal continue to be documented in high income countries around the world (McConnell et al, 2011;McConnell et al, 2020;LaLiberte et al, 2017;Llewellyn et al, 2003;Tøssebro et al, 2017). Studies utilizing data from the 2003 and 2008 Canadian Incidence Study of Reported Child Abuse and Neglect have found that, all else being equal (e.g., child, caregiver, household and case characteristics), the odds of child removal and court application are greater when parental CI is suspected or confirmed, in comparison with all other cases (McConnell, et al, 2011;McConnell, et al, 2020). McConnell et al (2020) found that primary caregiver CI was noted in 6.3% of all CPS cases (but 14.3% of all cases involving infants), 18.4% of cases where a child was removed, and 20.0% of cases culminating in a court application.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…An estimated 2.3% of parents in the United States have an intellectual and developmental disability (I/DD; Kaye, 2012). Research shows that children of parents with disabilities are at high risk for allegations of child maltreatment, foster care placement, and termination of parental rights, the first step in freeing children for adoption (Booth & Booth, 2004; DeZelar & Lightfoot, 2018; McConnell et al, 2020; White, 2015). Additionally, children of parents with I/DD are disproportionately represented in foster care compared to children of parents with other disabilities.…”
mentioning
confidence: 99%